The Correlation of Age with Thrombocytes and D-Dimer Values in COVID-19 Patients at Hospital X in Jakarta, Indonesia - Prasetyoningsih, Nanik; Gani, Ascobat (Kesmas, 2024)
Coronavirus disease (COVID-19), caused by the SARS-CoV-2 virus, spread globally, with research indicating that prognosis severity can be assessed by thrombocyte and D-dimer levels; while, patient age serves as a mortality predictor. This study aimed to analyze the relationship between age with thrombocytes and D-dimer in COVID-19 patients. This cross-sectional study used laboratory testing samples from 667 COVID-19 patients at Hospital X in Jakarta, Indonesia, collected from August 2020 until May 2021. The data was collected using cluster random sampling and analyzed using descriptive statistics and the Chi square test (95% CI). The results showed that age and thrombocytes positively correlated with the D-dimer levels in COVID-19 patients (p-value